A new high voltage alluaudite sodium battery insertion material. (January 2023) - Barman, P.; Jha, P.K.; Chaupatnaik, A.; Jayanthi, K.; Rao, R.P.; Sai Gautam, G.; Franger, S.; Navrotsky, A.; Barpanda, P.
Abstract: Large-scale stationary storage forms a key sector that can be economically served by sodium-ion batteries. In realizing practical sodium-ion batteries, discovery and development of novel cathodes is essential. In this spirit, alluaudite -type Na2 Fe2 (SO4 )3 was reported in 2014 to have the highest Fe 3+ /Fe 2+ redox potential (∼3.8 V vs. Na). This finding led to reports on various PO4 3− and SO4 2− based alluaudite compounds exhibiting high energy densities. In 2017, MoO4 2− based alluaudite, Na2.67 Mn1.67 (MoO4 )3, was found as a 3.45 V cathode material. Exploring molybdenum chemistry further, this work reports alluaudite type Na3.36 Co1.32 (MoO4 )3 (NCMo) as a novel versatile electroactive cathode for Li-ion and Na-ion batteries. It was synthesized by a wet solution-combustion route with a restricted annealing duration of 1 min at 600 °C. Calorimetric study revealed the formation enthalpy from component oxides (ΔH°f, ox = −575.49 ± 7.75 kJ/mol) to be highly exothermic. Unlike the sulfate class of alluaudites, this material is highly stable in air and moisture (ΔHds = 537.42 ± 0.78 kJ/mol). Having an ionic conductivity of 6.065 × 10 −8 S/cm (at 50 °C), it offers a pseudo two-dimensional Na + migration pathway. Without any material optimization, NCMo was found to work as a high-voltage insertion cathode (ca. 4.0 V vs. Na/Na + and 4.1 V vs. Li/Li + ) in sync with theoretically predicted potential of 3.98 V (vs. Na/Na + ). Ex-situ X-ray diffraction and photoelectron spectroscopy studies revealed the occurrence of solid-solution redox mechanism solely involving Co 3+ /Co 2+ redox centre. It benchmarks Na3.36 Co1.32 (MoO4 )3 as a novel electrochemically active Mo-based alluaudite -type polyanionic cathode insertion material. Highlights: First demonstration of electrochemical activity in Na3.36 Co1.32 (MoO4 )3 alluaudite. High-voltage (4 V vs. Na, 4.1 V vs. Li) redox activity with Co 3+ /Co 2+ centre. Structure, thermochemistry and DFT analyses of Na3.36 Co1.32 (MoO4 )3 alluaudite.